Pattern of lipofuscin pigmentation in nitrergic and non-nitrergjc, neurofilament immunoreactive myenteric neuron types of human small intestine - Brehmer, Axel; Blaser, Barbara; Seitz, Gerhard; Schrödl, Falk; et al. (Histochemistry and Cell Biology, 2004)
Lipofuscin, an autofluorescent age pigment, occurs in enteric neurons. Due to its broad excitation and emission spectra, it overlaps with commonly used fluorophores in immunohistochemistry. We investigated the pattern of lipofuscin pigmentation in neurofilament (NF)-reactive nitrergic and non-nitrergic human myenteric neuron types. Subsequently, we tested two methods for reduction of lipofuscin-like autofluorescence. Myenteric plexus/longitudinal muscle wholemounts of small intestines of five patients undergoing surgery for carcinoma (aged between 18 and 69 years) were double stained for NF and neuronal nitric oxide synthase (nNOS). Lipofuscin pigmentation patterns were semiquantitatively evaluated by using confocal laser scanning microscopy with three different excitation wave lengths (one for undisturbed lipofuscin autofluorescence and two for specific labellings). Two pigmentation patterns could be detected in the five NF-reactive neuron types investigated. In nitrergic/spiny as well as in non-nitrergic/stubby neurons, coarse, intensely autofluorescent pigment granules were prominent. In non-nitrergic type II, III and V neurons, a fine granular, diffusely distributed and less intensely autofluorescent pigment was obvious. After incubation of wholemounts in either CuSO or Sudan black B solutions, unspecific autofluorescence could be substantially reduced whereas specific NF and nNOS fluorescence remained largely unaffected. We conclude that NF immunohistochemistry is useful for morphological representation of subpopulations of human myenteric neurons. The lipofuscin pigmentation in human myenteric neurons reveals at least two different patterns which can be related to distinct neuron types. Incubations of multiply stained whole mounts in both CuSO or Sudan black B are suitable methods for reducing autofluorescence thus facilitating discrimination between specific (immunohistochemical) and non-specific (lipofuscin) fluorescence.
Keywords: Age; Autofluorescence; Gut; Innervation